Integration of digital manufacturing skills in industrial design education and its impact on small and medium enterprises - Rapitsenyane, Yaone; Moalosi, Richie; Sealetsa, Oanthata Jester; Ruele, Victor; Mosepedi, Thatayaone; Matake, Botumile (Frontiers in Mechanical Engineering, 2023)
Manufacturing has provided growth and employment opportunities to many developed countries. Digital technologies have further enhanced these opportunities and diversified manufacturing activities. However, it has not been as successful in developing countries, such as Botswana, due to the low absorptive capacity, lagging digital infrastructure, and the slow development of people who need upskilling or an entirely new skill set. The increase in access to the Internet and the extensive adoption of information and communication technologies by manufacturing companies are driving competition and disrupting the present circumstances. This study aims to assess the digital skills students acquire when studying an industrial design programme and compare them with the skills needed by digital manufacturing small and medium enterprises. A case study was adopted for this study because it can capture the relationship among the phenomena, context, and people in the lived realities of the participants. The findings indicate an alignment of the skills students acquire during their studies with those needed by digital manufacturing small and medium enterprises. However, the level at which students are exposed to these digital manufacturing skills is skewed towards basic awareness, with very few students reporting competency in digital manufacturing skills, such as using a laser cutter, plasma cutter, 3D printing, and a router machine. The emphasis could be shifted to developing digital manufacturing skills, as this is the future of manufacturing in the fourth and fifth industrial revolutions.